Temperature estimation of water cooling stator windings considering twisted structure and resistance distribution. Issue 3 (11th November 2021) - Bian, Xu; Zhao, Yan; Liang, Yanping
Abstract: The twisted structure of strand is ignored and the resistance of all parallel copper strands is assumed to be at the same temperature in existing temperature estimation method of water cooling stator windings. However, the twisted structure leads to the changing of thermal source and cooling structure, the uneven thermal distribution of parallel copper strands leads to uneven resistance distribution, both of which will influence thermal distribution of stator windings and should be considered in the temperature estimation method. In this study, the temperature estimation method considering twisted structure and uneven resistance distribution is first proposed, called three‐dimensional (3‐D) network method, in which the nodes of circuit network and thermal network are completely consistent. Then, the water cooling stator winding of a 1240‐MW turbo generator is taken as an example, the thermal distribution of which are calculated by the proposed method and validated by both short‐circuit type test data and 3‐D finite element method (FEM). Finally, the influence of twisted structure and resistance distribution on the thermal distribution is analysed in detail. The results show that the twisted structure has a great effect on thermal distribution, which cannot be ignored, while the resistance distribution has little effect on thermal distribution.